2019
DOI: 10.1029/2019gl082591
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Limits Carbon in Liquid Iron

Abstract: Melting experiments were performed on the Fe‐C‐H system to 127 GPa in a laser‐heated diamond anvil cell. On the basis of in situ and ex situ sample characterizations, we found that the solubility of carbon in liquid Fe correlates inversely with hydrogen concentration at ~60 GPa and ~3500 K, indicating that liquid Fe preferentially incorporates hydrogen rather than carbon under conditions with abundant C and H. While large amounts of both C and H may have been delivered to the growing Earth, C‐poor/H‐rich metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 51 publications
(98 reference statements)
3
69
0
Order By: Relevance
“…However, these possibilities are less likely. The water content of the core remains controversial (e.g., Clesi et al., 2018; Hirose et al., 2019; Iizuka‐Oku et al., 2017; Li et al., 2020; Okuchi et al., 1997; Terasaki et al., 2012; Yuan & Steinle‐Neumann, 2020), but it is most likely not decreasing over time, making it an unlikely source of an increase in mantle water. Possible hydrous partial melts in the early mantle would have likely been too buoyant to remain gravitationally stable at depth (Mookherjee et al., 2008) and would have erupted to release their water onto the surface.…”
Section: Resultsmentioning
confidence: 99%
“…However, these possibilities are less likely. The water content of the core remains controversial (e.g., Clesi et al., 2018; Hirose et al., 2019; Iizuka‐Oku et al., 2017; Li et al., 2020; Okuchi et al., 1997; Terasaki et al., 2012; Yuan & Steinle‐Neumann, 2020), but it is most likely not decreasing over time, making it an unlikely source of an increase in mantle water. Possible hydrous partial melts in the early mantle would have likely been too buoyant to remain gravitationally stable at depth (Mookherjee et al., 2008) and would have erupted to release their water onto the surface.…”
Section: Resultsmentioning
confidence: 99%
“…10.1029/2020GL088303 reflects exsolved hydrogen during quench due to its low solubility in solid Fe at ambient conditions (Antonov et al, 1998(Antonov et al, , 2019Fukai & Suzuki, 1986). Hirose et al (2019) and Umemoto and Hirose (2020) similarly arrive at the conclusion that the experiments by Clesi et al (2018) and Malavergne et al (2019) underestimate the hydrogen content in the metal.…”
Section: Figurementioning
confidence: 99%
“…However, recent metal-silicate partitioning experiments by Clesi et al (2018) and Malavergne et al (2019) found hydrogen to be lithophile at high P and T, which shifted the debate of hydrogen in the Earth's core. Determining the hydrogen content of the metal in such experiments remains challenging as FeH x decomposes during sample recovery from high P and T. Also, graphite was used as sample capsules, and recent DAC experiments (Hirose et al, 2019) suggest that C and H are mutually exclusive in molten iron. The presence of carbon may reduce the hydrogen storage capacity of iron, resulting in a very small equilibrium constant K D between molten iron and silicate melt…”
Section: Introductionmentioning
confidence: 99%
“…This prediction was based on experimental observations that the x value became constant above 10 GPa [179,180]. However, Pepin et al [181] reported new FeHx phases with x = 2 and 3 at 67 and 86 GPa, respectively, observed upon laser heating in DAC, which was later supported by Hirose et al [182] to 127 GPa. As such, the compositional range of the solid-solution is expanding as the system is explored further.…”
mentioning
confidence: 96%